2021
DOI: 10.3390/nu13093046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Features of Celiac Disease in a Cohort of Italian Children with Autism Spectrum Disorders

Abstract: Background: Autism spectrum disorders (ASD) are a heterogeneous group of neurodevelopmental conditions whose etiopathogenesis derives from a complex interaction between genetic liability and environmental factors. In this framework, mounting evidence suggests that immune system dysfunction could be a risk factor contributing to the development of ASD in at least a subpopulation of individuals. In particular, some studies suggest an association between celiac disease (CD)—a long-term autoimmune disorder that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
8
1
Order By: Relevance
“…For example, the data concerning the contribution of celiac disease and gluten intolerance is currently controversial. There is limited evidence of an association between celiac disease and ASD [ 77 ], and the prevalence of celiac disease was not found to be higher in an ASD population in comparison to that in a control group [ 78 ]. However, it may be that in the presence of ASD, celiac disease presents in an atypical way [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the data concerning the contribution of celiac disease and gluten intolerance is currently controversial. There is limited evidence of an association between celiac disease and ASD [ 77 ], and the prevalence of celiac disease was not found to be higher in an ASD population in comparison to that in a control group [ 78 ]. However, it may be that in the presence of ASD, celiac disease presents in an atypical way [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence of an association between celiac disease and ASD [ 77 ], and the prevalence of celiac disease was not found to be higher in an ASD population in comparison to that in a control group [ 78 ]. However, it may be that in the presence of ASD, celiac disease presents in an atypical way [ 78 ]. There is also convincing evidence of a positive and significant association between ASD and allergic conditions, especially food allergy [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence supports the idea that immune system malfunction may play a role in the etiology of ASD for certain people [55]. CD, an autoimmune ailment that mostly affects the small intestine and is driven by gluten consumption, has been linked to ASD by some research while others have shown a random relationship between the two conditions [54,55].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…It also discovered data that supported the existence of gut-immune-brain linkages by revealing the presence of specific causal interactions. Future research that incorporates large prospective designs and objective and standardized GID measurements will be required to gain a more nuanced knowledge of GID's function in ASD [54].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%